2005
DOI: 10.1002/ijc.21437
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk among patients with multiple sclerosis: A population‐based register study

Abstract: Cancer occurrence in patients with multiple sclerosis (MS) has been little studied, but associations with brain tumours, breast cancer, Hodgkin lymphoma and nasopharyngeal carcinoma have been suggested. We took advantage of population-based registers of MS and cancer to assess the risk of cancer following diagnosis of MS. Patients registered in the Danish Multiple Sclerosis Register were linked with the Danish Cancer Register to obtain information on cancer occurrence. The ratio of the observed to the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
144
4
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(160 citation statements)
references
References 46 publications
9
144
4
2
Order By: Relevance
“…The number of MS observed corresponds roughly to what is expected for Denmark [14]. We have no explanation for the discrepancy.…”
Section: Page 3 Ofsupporting
confidence: 72%
See 1 more Smart Citation
“…The number of MS observed corresponds roughly to what is expected for Denmark [14]. We have no explanation for the discrepancy.…”
Section: Page 3 Ofsupporting
confidence: 72%
“…A previous Danish report [14] did not find an increased incidence of CNS cancers among MS patients. Because our MS patients were hospitaltreated there could be a tendency that these were the more serious cases.…”
Section: Discussionmentioning
confidence: 56%
“…Findings from large MS cohorts suggest that the risk of cancer is reduced in MS patients compared with that of the general population [17,18], and cancer-associated mortality has also been found to be lower in MS [19]. Other studies have reported gender-specific risk reductions in women [20] and for men with MS [21]. Lower than expected rates of specific cancers have also been found, including skin malignancies [22] and digestive organ malignancies [23].…”
mentioning
confidence: 99%
“…Tian és mtsai nem mutattak ki meg- növekedett esélyt emlőkarcinóma kialakulására RA-s betegeknél [54]. Mások a sclerosis multiplex és az emlőrák kapcsolatát vizsgálva szintén gyenge korrelációt találtak [55].…”
Section: Az öSztrogénmetabolitok Autoimmun Betegségekre Kifejtett Hatunclassified